Comprehensive control model of soil and water conservation in Pisha stone area. Issue 1 (June 2020) - Shen, Zhenzhou; Yao, Wenyi; Xiao, Peiqing; Li, Mian; Rao, Liangyi; Li, Xiaolong; Li, Changing; Weiweichen,; wu, Yan; yang, Jishan; Jing, Chengran; Jiao, Peng; et al.
Abstract: Base the research of landform, soil erosion and vegetation characteristics, the comprehensive control model of soil and water conservation is summarized in Pisha stone area. The dates shows that: The general idea of this area is to take the construction of gully dam system as the starting point and to strengthen the construction of gully dam system with the main project of gully control. In line with local conditions, we will actively promote the construction of forest and grass vegetation, return farmland to forest and grassland, and implement large areas of closure and control, so as to give full play to the self-repair function of the ecosystem.